(NwYRA]IWANIE KRISTALLOW METODOM RADIACIONNOGO NAGREWA(B. (NoKSIDNYE SISTEMY (B/s - (NaRSENXEW(B, (NpAWEL aLEKSANDROWI^s; d ut9; (NfAZILOW(B, (Na(B.s; (NfENIN(B, (Nw(B.(Nw(B.s; (NtANANAEW(B, (NiWAN wLADIMIROWI^s; (NfIZIKO(B-(NTEHNI^ESKIJ IN(B-(NT IM(B. (Ns(B.(Nw(B. (NsTARODUBCEWAs ((NtA[KENT (B:s (NfAN(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 136-155 (412 (NNAZW(B.)s
Keywords: (NwYRA]IWANIEs; (NkRISTALLYs; (NmETALLY(B, (NOKISLYs; (NnAGREW RADIACIONNYJs